Whole patient knowledge modeling of COVID-19 symptomatology reveals common molecular mechanisms - Brock, Stephan; Jackson, David B.; Soldatos, Theodoros G.; Hornischer, Klaus; Schäfer, Anne; Diella, Francesca; Emmert, Maximilian Y.; Hoerstrup, Simon P. (Frontiers in Molecular Medicine, 2023)
Infection with SARS-CoV-2 coronavirus causes systemic, multi-faceted COVID-19 disease. However, knowledge connecting its intricate clinical manifestations with molecular mechanisms remains fragmented. Deciphering the molecular basis of COVID-19 at the whole-patient level is paramount to the development of effective therapeutic approaches. With this goal in mind, we followed an iterative, expert-driven process to compile data published prior to and during the early stages of the pandemic into a comprehensive COVID-19 knowledge model. Recent updates to this model have also validated multiple earlier predictions, suggesting the importance of such knowledge frameworks in hypothesis generation and testing. Overall, our findings suggest that SARS-CoV-2 perturbs several specific mechanisms, unleashing a pathogenesis spectrum, ranging from ‘a perfect storm’ triggered by acute hyper-inflammation, to accelerated aging in protracted ‘long COVID-19' syndromes. In this work, we shortly report on these findings that we share with the community via a) a synopsis of key evidence associating COVID-19 symptoms and plausible mechanisms, with details presented within b) the accompanying ‘COVID-19 Explorer’ webserver, developed specifically for this purpose (found at https://covid19.molecularhealth.com). We anticipate that our model will continue to facilitate clinico-molecular insights across organ systems together with hypothesis generation for the testing of potential repurposing drug candidates, new pharmacological targets and clinically relevant biomarkers. Our work suggests that whole patient knowledge models of human disease can potentially expedite the development of new therapeutic strategies and support evidence-driven clinical hypothesis generation and decision making.